Designing Kitabah Point: Gamified ClassPoint Integration for Enhancing Arabic Writing Skills in Secondary Schools - Fajar Ayu Syahfitri; Zukhaira Zukhaira; Mohamad Yusuf Ahmad Hasyim (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2026)
This research aims to develop Arabic learning media using gamification features on the ClassPoint platform, integrated with Microsoft PowerPoint. This type of research utilizes a research-and-development approach with the DDD-E (Decide, Design, Develop, and Evaluate) model. The subjects of this study are 77 students of class X from MAN 1 Boyolali, MAN 2 Boyolali, and MA Al Ihsan Doglo; Arabic language materials and media; Arabic subject teachers; Arabic lesson books for class X; short interviews; and media assessment sheets. The results of the initial analysis indicated that students need Arabic learning media in digital forms. This product encompasses subject matter and its evaluation, with a focus on writing skills and utilizing the ClassPoint feature. The results of validation by material and media experts indicate that this Kitabah Point media is suitable for use, with an average value of 93.5%, suggesting a very feasible interpretation. This Kitābah Point media can be used to learn Arabic in an interactive environment and is more fun because it uses an Android smartphone.